Emerging Pedagogies for Policy Education
XXI, 254 p. 26 illus., 20 illus. in color.
Keywords: “This book focuses on the importance of quality curriculum and pedagogy to support policy education in a complex and technologically connected world. The volume is valuable due to its recognition of the interplay between content knowledge and pedagogical knowledge, within the teaching and learning context. The authors contribute careful and varied examples of curriculum and pedagogical strategies that are useful for public policy educators in higher education. The specific focus on situated practice in Asia is particularly interesting and provides a refreshing and original contribution to the literature.” --Tricia Seow, National Institute of Education, Nanyang Technological University, Singapore “This is an important book that I recommend to public policy educators and scholars as well as those interested in designing multi-and-interdisciplinary curriculum and pedagogical strategies that have implications for all forms of decision making.” --Eduardo Araral, Lee Kuan Yew School of Public Policy, National University of Singapore, Singapore This edited book captures key trends that are driving changes in policy education and presents a repertoire of pedagogies to prepare educators and policy programme designers to teach for better impact in learning and policy practice. Supported with observations from selected Asian universities the chapters cover the experiences of authors in working with students at undergraduate and postgraduate levels, as well as professional programmes such as executive education, training, and capacity building for mid-career professionals and practitioners. Part I of this book presents ideas that are asserting the need for incorporation of new content as well as teaching practices for policy education. Part II covers selected cases of application of pedagogical approaches and strategies in Asian universities, tested at different education levels, modes of teaching, and disciplines. Sreeja Nair is Assistant Professor at the Lee Kuan Yew School of Public Policy, National University of Singapore. With a specialization in environmental policy, she studies policy processes and tools of governments to address uncertainty in policymaking. Her research focuses on Asia and covers diverse environmental and socio-technical policy issues, including climate change, food security and more recently, digital transformation. Navarun Varma is Lecturer (Resident Fellow) and Assistant Director of External Programmes at Residential College 4, National University of Singapore. He specializes in teaching and research on interdisciplinary topics related to disaster resilience and environmental governance.